Biotransformation of Carvedilol Using Plant Cell Culture of Decalepis hamiltonii and Nicotiana tabacum - Shekar, Ch. Raja; Rao, Ajmera Rama; Patil, Umesh K; Veeresham, Ciddi (Indian Journal of Natural Products, 2022)
The biotransformation reaction of cell suspension cultures produced from Decalepis hamiltonii and Nicotiana tabacum leaves were investigated, using Carvedilol drug. Interestingly, the cell suspension cultures showed biotransformation of racemic carvedilol. There is noticeable conversion of S-enantiomer to R-enantiomer of Carvedilol. The bio-conversion was detected and quantified by Chiral HPLC. The ideal biotransformation was achieved with the concentration of 0.1mg/ml Carvedilol at pH 5.8. The optimum incubation time was observed to be 15 days The Decalepis hamiltonii and Nicotiana tabacum cell culture have shown the capacity to convert S-isomer to R-isomer, because it has enzymes specific for conversion from S to R form. Among the two plants Decalepis hamiltonii have shown better biotransformation when compared to Nicotiana tabacum.
Keywords: Bio transformation; HPLC; Plant cell cultures; Carvedilol; Nicotiana tabacum